THE EVOLUTION OF THE NATURAL PROTECTED AREAS NETWORK IN ROMANIA - SORIN GEACU; MONICA DUMITRAŞCU; IURIE MAXIM (Revue Roumaine de Géographie)
The paper is aiming to present a historical overview of the Romanian protected areas network starting with the earliest initiatives on nature conservation and the establishment of first natural reserves in 1932. The authors have identified several stages in the dynamics of natural protected areas which, over the last two decades, havedoubled in number and grew in surface up to eight times. Currently, Romania natural protected areas totalizes up to 1,798,782 ha, thus representing 7.55% of the national territory. According to UICN they frame into the following categories: national parks (13), natural parks (15), biosphere reserves (3), scientific reserves (79), natural monuments (230) and nature reserves (661). Additionally, in 2007 national network “Natura 2000” was created as part of the European Ecological Network. At present, Natura 2000 in Romania includes 408 Sites of Community Importance and 148 Special Protection Areas, with a total area of 74,494,000 hectares.